"Skip the infection, get the injection": A case study in emergency preparedness education. Issue 1 (January 2015) - Adams, Lavonne M.; Canclini, Sharon B.; Frable, Pamela Jean
Abstract: The frequency of natural and manmade disasters along with increasing potential for public health emergencies emphasizes the need for emergency preparedness education. Because nurses are the largest group of health professionals to meet the needs of those affected by disasters and public health emergencies, schools of nursing need to prepare graduates who are knowledgeable about disaster and public health emergency management. The use of core competencies may be a means to ensure consistent application of best practices in disaster health care. The next step in competency development involves validation through evidence. Through documentation and dissemination of their experiences with emergency preparedness education, schools of nursing can provide supportive evidence to aid in competency development. The purpose of this paper is present a case study of an ongoing and evolving public health nursing education project consistent with disaster health care and emergency preparedness competencies.